Potencial de produtos dessensibilizantes em reduzir a difusão do peróxido de hidrogênio em dentes com lesões cervicais não-cariosas - Sánchez, Carlos Andrés Dávila (2014)
The aim of this in vitro study was to evaluate the occlusive potential of three commercial desensitizing toothpastes by atomic force microscopy before and after bleaching, and quantify the hydrogen peroxide (HP) diffusion to the pulp chamber after application of these products in teeth with artificial cervical lesions (ACL). Sixtyfive human extracted premolars were used to measure PH diffusion. In fifty-two teeth, artificial 2-mm deep ACL were prepared, and an EDTA solution was applied for 10 s and rinsed with distilled water. Then, teeth were adapted in a brushing machine and brushed with a constant loading (250 g; 4.5 cycles/s; 3 min) with a regular toothpaste with no occlusive compounds (Colgate Cavity Protection) and occlusive toothpastes (Sensodyne Rapid Relief, Colgate ProRelief and Oral-B Pro Health). In thirteen teeth (control group), no ACL was prepared and they were stored in distilled water. After that, teeth from both experiments were bleached with 35% HP with three 15-min applications. The HP diffusion was measured spectrophotometrically by the reaction of HP with 4-aminoanthipyrin and phenol at a wavelength of 510 nm and the ACL were evaluated before, after toothbrushing and after bleaching by AFM. Four sound molar were used and subjected to each one of the dentifrices for the AFM test. Data from each experiment was subjected to one-way ANOVA and Tukey´s test (α = 0.05). All groups with ACL, regardless of the toothpaste employed, showed higher HP penetration than the sound teeth (p < 0.001).